Should Subsidized Private Transfers Replace Government Social Insurance? - Fullenkamp, Connel; Chami, Ralph (Washington, D.C. : International Monetary Fund, 2000)
Private transfers between individuals or through organized charities are increasingly viewed as an alternative for government social insurance programs. This paper models the incentive effects of government subsidized private transfers and finds that while there is a significant welfare benefit to subsidizing private transfers, there is also a significant welfare cost to this policy. It is shown analytically, as well as through simulations, that the optimal subsidy to private transfers is positive for a wide range of parameter values. This result indicates that subsidized private transfers in net terms are welfare enhancing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet